Gender Diversity, Capital Structure and Financial Performance: A study of Banks in the UK - Laka, Daniel Temitope; Mamodu, Jesse David; Laka, Unenwojo Folaolurin (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
This study aims to explore the effect of gender diversity on the capital structure and financial performance of listed banks in the UK, covering a 10-year period from 2011 to 2020 and using a sample of 11 banks. To test the effect of gender diversity on capital structure and financial performance, the ordinary least square regression was employed. Debt-to-equity ratio was used as a measure of capital structure, while financial performance was measured using Tobin’s q. Board gender diversity was found to have a negative and significant effect on UK banks’ capital structure. On the other hand, board gender diversity had a positive and significant effect on the financial performance of UK banks, all at a 10% level of significance. It is therefore concluded that gender diversity will be significant in driving the economy, especially following the current economic strain caused by the pandemic. It is recommended that more strategies to encourage more women on the board should be encouraged.